Loss of CG Methylation in Marchantia polymorpha Causes Disorganization of Cell Division and Reveals Unique DNA Methylation Regulatory Mechanisms of Non-CG Methylation. (9th August 2018) - Ikeda, Yoko; Nishihama, Ryuichi; Yamaoka, Shohei; Arteaga-Vazquez, Mario A; Aguilar-Cruz, Adolfo; Grimanelli, Daniel; Pogorelcnik, Romain; Martienssen, Robert A; Yamato, Katsuyuki T; Kohchi, Takayuki; Hirayama, Takashi; Mathieu, Olivier
Abstract: DNA methylation is an epigenetic mark that ensures silencing of transposable elements (TEs) and affects gene expression in many organisms. The function of different DNA methylation regulatory pathways has been largely characterized in the model plant Arabidopsis thaliana. However, far less is known about DNA methylation regulation and functions in basal land plants. Here we focus on the liverwort Marchantia polymorpha, an emerging model species that represents a basal lineage of land plants. We identified Mp MET, the M. polymorpha ortholog of the METHYLTRANSFERASE 1 ( MET1 ) gene required for maintenance of methylation at CG sites in angiosperms. We generated Mp met mutants using the CRISPR/Cas9 (clustered regularly interspaced short palindromic repeats/CRISPR-associated protein9) system, which showed a significant loss of CG methylation and severe morphological changes and developmental defects. The mutants developed many adventitious shoot-like structures, suggesting that Mp MET is required for maintaining differentiated cellular identities in the gametophyte. Even though numerous TEs were up-regulated, non-CG methylation was generally highly increased at TEs in the Mp met mutants. Closer inspection of CHG methylation revealed features unique to M. polymorpha. Methylation of CCG sites in M. polymorpha does not depend on MET1, unlike in A. thaliana and Physcomitrella patens. Our results highlight the diversity of non-CG methylation regulatory mechanisms in plants.